2011
DOI: 10.1007/s11010-011-1169-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned medium from hypoxic cells protects cardiomyocytes against ischemia

Abstract: The hypothesis of the present study is that cardiomyocytes subjected to prolonged ischemia, may release survival factors that will protect new cardiac cells from ischemic stress. We exposed neonatal rat cardiomyocyte primary cultures to hypoxia, collected the supernatant, treated intact cardiac cells by this posthypoxic supernatant, and exposed them to hypoxia. The results show cardioprotection of the treated cells compared with the untreated ones. We named the collected posthypoxic supernatant "conditioned me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…In the gradient condition, a pattern emerged that the normoxic side was typically more dysfunctional than the hypoxic side. Previous studies with conditioned medium have shown that hypoxic CMs secrete factors that can protect other CMs from ischemic stress ( 66 ). Thus, in the gradient tissues, hypoxic and normoxic CMs may be continuously exchanging factors that contribute to the observed phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…In the gradient condition, a pattern emerged that the normoxic side was typically more dysfunctional than the hypoxic side. Previous studies with conditioned medium have shown that hypoxic CMs secrete factors that can protect other CMs from ischemic stress ( 66 ). Thus, in the gradient tissues, hypoxic and normoxic CMs may be continuously exchanging factors that contribute to the observed phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this effect was found to be as potent as that induced by EPC transplantation 35 . In more recent studies, hypoxic CM from cardiomyocyte hypoxic cultures was shown to protect isolated hearts against ischemia, reducing infarct size and improving the rate of contraction and relaxation, 36 while hypoxic CM from ASCs stimulated angiogenesis in subcutaneously implanted sponges to a greater extent than normoxic CM, an effect associated with increased paracrine VEGF and ANG production by hypoxic ASCs 37 …”
Section: Strategies Based On Hypoxic Pre-conditioning In Vitromentioning
confidence: 97%
“…Soluble paracrine factors present in secretome have been shown to have an antiapototic paracrine effect essential for the improvement of heart function post-infarction. 26 For this reason, the antiapoptotic paracrine effect of the secretome loaded nanocomposite hydrogels was another focus of this study.…”
mentioning
confidence: 99%